Effects of Curcumin on Changes in Spermatogenetic Cells of Rats Treated with Cisplatin - Şengül Şentürk; Mustafa Sandıkçı (Poltekkes Kemenkes Banjarmasin Jurusan Analis Kesehatan, 2022)
Cisplatin is an effective antineoplastic drug which is used to treat many types of cancer. The most common known side effect of this drug is infertility. Curcumin, also called turmeric, has antioxidant and antitumor activities. This study was designed to investigate the effects of curcumin on the changes in spermatogenetic cells caused by cisplatin, which is used as a chemotherapeutic drug especially in testicular cancers. For this purpose, randomly selected 36 Spraque Dawley rats were seperated to 4 groups that of control, cisplatin, curcumin and curcumin+cisplatin and each group was seperated to 3 subgroups, each of them have 3 rats, so total 12 subgroups were obtained. The testicular tissues obtained from rats were evaluated histochemically, immunohistochemically and ultrastructually. In the results of this study, it is observed that the rate of apoptosis increased significantly in the experimental groups given curcumin together with cisplatin injection, and the transition-1 protein which is involved in DNA packaging in the elongated spermatids belonging to stages of XII, XIII an XIV, immunopositivity is increased statistically in the cisplatin-administered experimental groups compared to control groups. Both light and electron microscopic findings showed that intense degeneration, vacuolization, germ cell loss and spermatogenetic arrest occurred especially in the group given curcumin together with cisplatin. The results of our study showed that cisplatin can cause problems in infertility through DNA packaging and dragging cells to apoptosis and necrosis. Physicians who use cisplatin for cancer treatment are advised not to use curcumin together with cisplatin because it exacerbates the side effects of the cancer drug.